Should the Application of Diode Laser Completely Replace Conventional Pulpotomy of Primary Teeth? - Luka Šimunović; Bruno Špiljak; Lara Vranić; Rebecca Bašić; Dubravka Negovetić Vranić (Applied Sciences, 2022)
Nowadays, the use of lasers in dental medicine has become an effective approach for numerous restorative and soft tissue therapeutic procedures. The use of different types of lasers depends on how the tissue interacts with the laser light and the purpose of treatment. Although some studies show the benefits of laser pulpotomy compared to the conventional method of pulpotomy, clinical studies are lacking. Moreover, the material used for a definitive restoration of endodontically treated primary teeth can also affect the outcome of the therapy. Therefore, this prospective study aimed to compare the clinical use of the diode laser and the conventional method of vital pulpotomy, as well as the influence of the material chosen for a definitive restoration for the outcome of the procedure. Patients were divided into two groups: conventional pulpotomy and 980 nm diode laser. Each group was then divided into two subgroups according to the type of material for the final restoration. By comparing the success of the therapy according to clinical parameters depending on the material of the final restoration, the advantage of the composite material compared to the glass ionomer cement was noticed at 6 months checkup (p = 0.045). A strong positive correlation between the quality of the final restoration according to the United States Public Health Service (USPHS) criteria and the success of the clinical parameters was found in all investigated time points. There is no statistically significant difference between the diode laser and the conventional pulpotomy, however, the choice and quality of the final restoration significantly contribute to the outcome of therapy.